2017
DOI: 10.5812/jhealthscope.63163
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Financial Protection in Hospitalized Patients after the Health Sector Evolution Plan in Iran

Abstract: Background: Protecting people from catastrophic health payments is widely recognized as an integral component of health systems and universal health coverage. Objectives: This study aimed to measure the financial protection against catastrophic health expenditure among hospitalized patients in Kermanshah, western Iran, after the implementation of the health sector evolution plan of Iran. Methods: This was a cross-sectional study. A total of 544 patients were selected using the proportional allocation to popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Based on the study results, as supported by other studies (10,13,14,18,25,26), there was an inverse relationship between facing CHE and increasing rank of economic quintiles among households. However, the findings of a study by Somkotra and Lagrada in 2009 disclosed that following the implementation of UHC in Thailand, CHE shifted from poor to rich households (24).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Based on the study results, as supported by other studies (10,13,14,18,25,26), there was an inverse relationship between facing CHE and increasing rank of economic quintiles among households. However, the findings of a study by Somkotra and Lagrada in 2009 disclosed that following the implementation of UHC in Thailand, CHE shifted from poor to rich households (24).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings showed that the mean OOP health expenditure for participants was $ 124. Two previous studies conducted after the HTP reported this figure as $ 24 and $ 39 (10,14). However, these figures are lower than what a study reported before the HTP (13).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations